EXPLORING THE USE OF ARTIFICIAL INTELLIGENCE IN PROMOTING ENGLISH LANGUAGE PRONUNCIATION SKILLS - Mohammadkarimi, Ebrahim (LLT Journal: A Journal on Language and Language Teaching, 2024)
This research examines the potential of artificial intelligence (AI) in enhancing learners' English pronunciation skills. The participants were 78 English language learners at the elementary and pre-intermediate levels, and 19 experienced English language teachers. The researcher employed a mixed-method approach, integrating both quantitative and qualitative data collection techniques, to comprehensively assess the efficacy of AI-based pronunciation aids and gauge learners' perceptions. During a course of two months, the experimental group used Listnr and Murf AI tools, while the control group adhered to a conventional instruction. The data were taken from pre- and post-test pronunciation scores, questionnaire responses, and interviews with the individuals. The findings of the pre- and post-test indicated that the participants in the experimental group had significant improvements in their pronunciation accuracy. The participants in the study had mostly favorable attitudes towards AI-driven tools, emphasizing their effectiveness in enhancing pronunciation skills, boosting confidence, and promoting engagement. Nevertheless, several obstacles pertaining to the interpretation of feedback and the capture of subtle differences in pronunciation were recognized. This research has shown how AI can potentially be used to teach pronunciation effectively, and it has provided valuable insights for teachers, curriculum developers, and learners.